Pedagogical content knowledge as a model for academic development practice in the third space - Erik Brogt (Journal of Learning Development in Higher Education)
In this opinion piece, I make the case for the use of Shulman’s concept of Pedagogical Content Knowledge as both a practical and philosophical approach to academic development work in the third space. I argue that a PCK-like model allows for the development of relationships with academics that are grounded in mutual respect for one another’s expertise and are collaborative in nature and provides guidance for the scope of academic development work. I also argue that using PCK as a model can enhance the credibility of third space workers as we navigate the political and managerial environment of a higher education institution.